1999
DOI: 10.1002/(sici)1097-4547(19990401)56:1<8::aid-jnr2>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for mitochondrial control of neuronal polarity

Abstract: An early and essential step in the formation of functional neuronal circuits is the establishment of cell polarity, a process involving the morphological and functional differentiation of the axon (axonogenesis). We now report that treatment of cultured embryonic hippocampal neurons with ethidium bromide (EtBr; an agent that depletes mitochondrial DNA), prior to the establishment of cell polarity, prevents axon formation while permitting outgrowth of minor processes. The polarity-suppressing action of EtBr occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Mitochondria play important roles in neuronal developmental processes, including the establishment of axon polarity and the regulation of neurite outgrowth (36,37). Since it has been reported that Vpr influences mitochondrial function in several cell types and induces mitochondrial membrane depolarization (5,25,26), Vpr also may induce mitochondrial dysfunction in neuronal progenitor cells.…”
Section: Inhibitionmentioning
confidence: 99%
“…Mitochondria play important roles in neuronal developmental processes, including the establishment of axon polarity and the regulation of neurite outgrowth (36,37). Since it has been reported that Vpr influences mitochondrial function in several cell types and induces mitochondrial membrane depolarization (5,25,26), Vpr also may induce mitochondrial dysfunction in neuronal progenitor cells.…”
Section: Inhibitionmentioning
confidence: 99%
“…Impaired Neuronal Outgrowth in NPC1Ϫ/Ϫ Neurons Is Restored by ATP Treatment in Culture-Because ATP is required for the development of neurons (32), the effect of NPC1 deficiency on neurite outgrowth was investigated using neurons prepared from cerebral cortices derived from NPC1ϩ/ϩ, NPC1ϩ/Ϫ, and NPC1Ϫ/Ϫ mouse brains. Using immunocytochemistry, the staining neurons for ␤-tubulin indicated that while neurite extension was clearly evident at 72 h in NPC1ϩ/ϩ and NPC1ϩ/Ϫ neurons, it was impaired in NPC1Ϫ/Ϫ neurons (Fig.…”
Section: The Level Of Cholesterol and Phospholipids In Cellular Fractmentioning
confidence: 99%
“…During the development, neuronal stem cells proliferate and differentiate into neurons; subsequently axons and dendrites form synapses [134][135]. The role of mitochondria in neuroplasticity is illustrated in Figure 3 [20].…”
Section: Mitochondria and Neuroplasticitymentioning
confidence: 99%
“…Nerve growth factor (NGF) was found as one of the signals inducing accumulation of mitochondria in the active growing cone [136]. Interestingly, when the ATP production is impaired and cells provide alternative source of energy, axogenesis is abolished although growth of dendrites remains relatively unaffected [134].…”
Section: Mitochondria and Neuroplasticitymentioning
confidence: 99%